Zinc supplementation could modulate T cell to maintain interleukin-2 level in seropositive contact of leprosy patients (Medical Journal of Indonesia, 2011)
Background: WHO classified the number of leprosy cases in Indonesia as number three in the world after India and Brazil. The number of new leprosy patients tends to increase since there is a possibility that seropositive leprosy is turning into manifest leprosy. The aim of this study was to analyze the influence of zinc supplementation on interleukin-2 (IL-2) level of seropositive contact of leprosy patients with marginal zinc deficiency. Methods: Twenty two subjects aged 20-40 years were recruited for this study. The zinc-supplemented group received 40 mg elemental Zn/d orally for 3 months. Seropositive leprosy was determined by examining IgM anti Phenolic Glycolipid-1 level and concentration of IL-2 in lymphocyte cell culture supernatant fluid were measured by Elisa method. Results: The IL-2 concentration in the subject in the zinc group was relatively not changed (p= 0.721), whereas that in placebo group tended to be significantly lower (p= 0.025) at the end of the study. Conclusion: There was a significant change of IL-2 level between both groups (p= 0.037). (Med J Indones 2011;20:201-4)